Building bridges: Content-teacher and language-teacher collaboration in South African high schools - Mpofu, Nhlanhla (Acitya: Journal of Teaching and Education, 2025)
In educational contexts where learners are instructed in a language different from their mother tongues, governments develop strategies to improve their proficiency in that language. This study examined how content and language integration was carried out in educational settings where English is used as the medium of instruction, focusing on multilingual South African high schools as the research sites to understand this phenomenon. The study included six participants grouped into three pairs, consisting of English teachers and content teachers from Economics and Life Sciences. Data were collected through lesson plan analysis, classroom observations and semi-structured interviews and analysed using inductive thematic analysis. The findings reveal three key themes: collaboration alignment for content and language learning; lesson planning collaboration; and collaboration focused on developing learning materials. The study suggests moving away from deficit-oriented approaches in content and language teaching and adopting an asset-based orientation that recognises and values learners’ strengths.